2021
DOI: 10.1002/jsfa.11269
|View full text |Cite
|
Sign up to set email alerts
|

Grain chalkiness traits is affected by the synthesis and dynamic accumulation of the storage protein in rice

Abstract: BACKGROUOND: Grain chalkiness lowers the market value of rice. Alleviating grain chalkiness is the most challenging issue in many rice-producing areas of the world. Nitrogen (N) metabolism has received increasing attention as a result of its relationship with grain chalkiness, although little information is available on the mechanism of N-induced grain chalk. RESULTS: A highly chalky rice variety OM052 was used to explore the protein synthesis and its accumulation in the grain exposed to N topdressing (N+) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Further research on the chalkiness of rice found that the generation of chalkiness is related to the carbon and nitrogen metabolism of rice, and the decrease in the activity of pyruvate orthophosphate dikinase is related to the chalkiness of rice [32]. The activity of proteinrelated synthase such as glutamine synthetase and glutamate synthase in rice 15 days after anthesis was correlated with rice chalkiness [33]. The chalkiness of the seven rice varieties we used showed the greatest changes.…”
Section: Discussionmentioning
confidence: 78%
“…Further research on the chalkiness of rice found that the generation of chalkiness is related to the carbon and nitrogen metabolism of rice, and the decrease in the activity of pyruvate orthophosphate dikinase is related to the chalkiness of rice [32]. The activity of proteinrelated synthase such as glutamine synthetase and glutamate synthase in rice 15 days after anthesis was correlated with rice chalkiness [33]. The chalkiness of the seven rice varieties we used showed the greatest changes.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the results also showed that the application of nitrogen fertilizer under elevated temperature could alleviate grain development, prolong the grain-filling period, and coordinate the development of amyloplasts and PBs (Figure 2), and it may be one of the main reasons for the decrease in chalkiness. However, Xi et al (2021) showed that nitrogen application at the panicle differentiation stage promoted the formation of chalky grains. This may indicate that the mechanism of the formation of chalkiness is relatively complicated, and physiological factors, genetic factors, and ecological factors could co-modulate its formation.…”
Section: Nitrogen Fertilizer Regulates Endosperm Development Under Elevated Temperaturementioning
confidence: 99%
“…Since both starch and proteins in grains are synthesized using sugar as the carbon source ( Bao et al., 2015 ; Xin et al., 2019 ), an optimal coordination between the C and N metabolism during grain filling is crucial, but less worked upon. Reports suggest that the nitrogen metabolism pathway and synthesis of storage proteins in particular may lead to grain chalk formation in rice ( Han et al., 2012 ; Xi et al., 2021 ). A significant negative correlation between prolamin content and chalkiness has also been discovered ( Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%